2014
DOI: 10.1016/j.egypro.2014.11.571
|View full text |Cite
|
Sign up to set email alerts
|

Application of CO2-Saturated Water Flooding as a Prospective Safe CO2 Storage Strategy

Abstract: In this study, According to the results of CO 2 solubility measurement tests at constant temperatures, an increase in CO 2 solubility values was observed for CO 2 -brine and CO 2 -oil systems when the equilibrium pressure increases. Furthermore, it was revealed that for both aforementioned systems, the solubility of CO 2 reduces when temperature increased. It was found that introducing CO 2 to the oil reservoirs through injection water provides great opportunity to lock large quantity of CO 2 inside the porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Injection of CO2-enriched water for enhanced oil recovery and CO2 storage has received substantial attentions amongst oil industry and CCS stakeholders [ (Blackford, 1987) (Christensen, 1961) (Oelkers, et al, 2008) (Alizadeh, et al, 2014) (Mosavat & Torabi, 2014)].…”
Section: Introductionmentioning
confidence: 99%
“…Injection of CO2-enriched water for enhanced oil recovery and CO2 storage has received substantial attentions amongst oil industry and CCS stakeholders [ (Blackford, 1987) (Christensen, 1961) (Oelkers, et al, 2008) (Alizadeh, et al, 2014) (Mosavat & Torabi, 2014)].…”
Section: Introductionmentioning
confidence: 99%
“…Shiflett et al, (2008) observed that the solubility of CO2 in ionic rich liquid shows unusual behaviors as CO2 dissolves in ionic liquid with no vapor pressure at low CO2 concentration but at high CO2 concentration there was immiscible layer (vapor-liquid equilibria). Mosavat and Torabi (2014) presented that increase in pressure leads to increase in the solubility of CO2 while increase in temperature leads to decrease in the solubility of CO2 in a CO2-brine system.…”
Section: Previous Workmentioning
confidence: 99%
“…This rise in the CO 2 retention in lignite core is absolutely due to the hysteresis effect during WAG cycle and a maximum of 53% of Sc-C has been retained in the lignite core plug. Soaking and solubility period of CO 2 saturated with the liquid phase, eventually, miscible and trap in the reservoir (Lee et al 2019;Pranesh et al 2018;Mosavat and Torabi 2014). Supercritical CO 2 ooding changes the rock geomechanical property and yield a high amount of storage (Zhang et al 2019b;Zhang et al 2017;Sander et al 2014;Zunsheng et al 2014).…”
Section: Hysteresis Modelling Of Co 2 Retention In Lignite Rockmentioning
confidence: 99%